Tinjauan terhadap Akuntabilitas Pengelolaan Dana Desa: Pengaruh Kompetensi, Kepemimpinan, Partisipasi Masyarakat, dan Pengawasan - Ratmono, Andrean Juli; Rusmana, Oman; Hasanah, Uswatun (Penerbit Goodwood, 2023)
Purpose: This study aims to elaborate and examines the influence of apparatus competence, leadership, community participation, and supervision on the accountability of perceived village fund management. Research methodology: This research is a case study using a quantitative approach. The research was conducted in 11 villages in Jatilawang District. The study population was members of the Village Government Institutions consisting of village officials and the Badan Permusyawaratan Desa (BPD) with a population of 215. The research sample was determined using a purposive sampling technique, with a total sample size of 110. Multiple linear regression was used for the data analysis. Results: The results of the study show that (1) Aparattus Competence has a positive and significant effect on perceived village fund management accountability, (2) leadership has a positive and significant effect on perceived village fund management accountability, (3) community participation has a positive and significant effect on perceived village fund management accountability, and (4) supervision has a on perceived village fund management accountability.